TRADITIONAL USES, PHYTOCHEMISTRY AND IN VITRO EVALUATION OF TOXICITY OF RICINODENDRON HEUDELOTII (BAILL PIERRE EX HECKEL) LEAVES IN BENIN. - GBAGUIDI, A. (My University, 2017)
The study is carried out in Benin in the municipalities of Kétou and Pobè, involving 156 individuals. Ethnobotanical, phytochemical and toxicological studies have been carried out on Ricinodendron heudelotii to evaluate endogenous knowledge on the use of the species in the Nago, Holli and Mahi ethnic groups, to identify the chemical groups characteristic of leave extracts and to evaluate in vitro their toxicity. The target groups know the species with an unequal distribution of knowledge for both ethnic groups and for age and sex categories. The Nago use much more Ricinodendron heudelotii for its artisanal properties, the Mahi for its food properties and the Holli for its medicinal properties. Phytochemistry reveals the great families of chemical groups (alkaloids, flavonoids, etc.) whose number and nature vary according to the provenance. The water-ethanolic extracts of the leaves have a half lethal concentration (LC50) higher than 0.1 mg / mL, and are therefore non-toxic on human cells.
Keywords: Ethnobotanical; Phytochemical screening; toxicity; Ricinodendron heudelotii; Benin.